(3JGQN HZOGOs - (3GdNWjH GdHZOGOjs; (3CMeO Hf Ydj Hf KGHJ GdHZOGOj, CHhHcQ,GdNWjH GdHZOGOj,J (B463 (3g` s
(3ChdgG (B:s
(3hjHOC GdehLhO efg HJQLeI (B" (3CMeO Hf LYaQ Hf CHj MaU , CHj GdaQL GdeYQha HGdfSGFi s
(3BNQgG (B:s
(3BNQ GdehLhO efg JQLeI (B" (3CMeO Hf eYQha Hf HSQ Hf ehSi CHj GdMSf GdNTGH s
(3ai NJGe cd LRA YOI SeGYGJ LSOI CbOegG SfI (B508 (3Je JhGQjN cKjQI Ydi GeJOGO GdbQf GdSGOS hYdi GdfSNI NWhs
(3eLdO efg jJVef JQGLe (B" (3GdCMeOjf (B" (3hjTJed Ydi GdCLRGA ef GdKGdK hGdKdGKjf Edi CKfGA GdCQHYjf hai hSW GdeLdO YTQ hQbGJ eOShSI ef JQGLe GdeMeOjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B172s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdJGQjNs